THE IMPACT OF CONCUSSION ON CARDIAC AUTONOMIC FUNCTION: A SYSTEMATIC REVIEW OF EVIDENCE FOR RECOVERY AND PREVENTION. Issue 7 (11th March 2014) - Blake, T; McKay, C; Meeuwisse, WH; Emery, C
Abstract : Background: Concussions can negatively impact cognitive, behavioural, and physiological function. The current standard of care does not account for the physiological impact of concussion. Cardiac autonomic function (CAF) is responsive to changes in physical and cognitive exertion in healthy populations. The influence of concussion on CAF is not well understood. Objective: To evaluate the evidence regarding the effect of concussion on cardiac autonomic function. Design: Systematic Review. Setting: Databases [Medline, SportDiscus, HealthSTAR, PsycINFO, Web of Science, CINAHL, Cochrane Central Register of Controlled Trials, EMBASE, PubMed and ProQuest, Web of Science and Google Scholar] were systematically searched using keywords and MeSH terms. Sample: Inclusion criteria: original research, available in English, included participants with concussion or mild traumatic brain injury (mTBI) and had a comparison group. Studies of humans (greater than 6 years old) and animals were included. Ten articles were identified for critical appraisal (six cohort studies, four cross-sectional). Independent variable: Diagnosis of a concussion or mTBI. Main outcome measurements: Heart rate (HR) and/or heart rate variability (HRV). Critical appraisal was conducted using the Downs and Black criteria. Results: There is conflicting evidence regarding CAF at rest following concussion/mTBI. There is evidence of elevated HR and reduced HRV with low intensity, steady-state exercise up to 10 days following concussion. No significant difference in HRV was found during isometric handgrip testing following concussion. The validity of current literature is limited by small sample sizes, lack of female or pediatric participants, varying methodologies and lack of follow-up. No studies evaluating CAF during cognitive exertion following concussion were found. Conclusions: There is evidence to suggest that CAF is altered during physical activity following concussion. The limitations in available literature highlight the need further research. Understanding the effect of concussion on CAF will contribute to the development of more comprehensive concussion management and prevention strategies.